High-resolution coral Ba/Ca records from the Great Barrier Reef - Juan Pablo D extquotesingleOlivo; Malcolm T McCulloch (PANGAEA, 2022)
High-resolution trace element data (Ba/Ca, Sr/Ca and U/Ca) from ten coral records collected from multiple locations in the Great Barrier Reef. The near weekly resolution trace element multi-decadal recrods were generated by analysing the skeleton of Porites corals by Laser Ablation Inductively Coupled Plasma Mass Spectrometer (LA ICP-MS). The generated Ba/Ca records used to reconstruct sediment concentration associated with river plumes reaching coral reefs, the Sr/Ca and U/Ca data were used to establish an age model.